Not all angels : an ecofeminist reading of dualism, domination and rebellion within The Hunger Games : a thesis presented in partial fulfilment of the requirements for the Masters of Creative Writing at Massey University, Albany, Aotearoa New Zealand. EMBARGOED until 17th February 2027. - Clark, Brittany (Massey University, 2025)
This thesis is comprised of two sections: a critical section analysing the young adult, speculative novel ‘The Hunger Games’ by Suzanne Collins, through the lens of ecofeminist theory, and the initial 24’600 words of a 60,000 word novel of the same genre entitled: ‘Above Ground’. Both sections explore the young, female protagonist and her relationship with individualism, dualism, rebellion, nature, and the dominance that presents itself alongside these themes. In the critical portion of the thesis, I outline the concepts of speculative fiction, ecofeminist theory, western dualisms such as the Nature vs Reason dualism, and the Angel in the eco system construct. I utilise these concepts in my close reading and literary criticism of The Hun ger Games (2008) by Suzanne Collins by analysing where they are present or could be observed within the novel. I then continue this close reading through an examination of the novel through an ecofeminist lens. I draw from the work of theorists such as Val Plumwood, Greta Gaard, Carol J. Adams, and Patrick D. Murphy to support my argument that The Hunger Games protagonist Katniss Everdeen, challenges dualistic structures of dominance that link the oppression of women with the exploitation of nature, within the narrative. By rejecting the "Angel in the Ecosystem" trope, Katniss reveals how both dominance and environmental manipulation are interlinked. This highlights the interconnectedness of dualism, othering, ecological abuses, and societal control. In applying ecofeminist theory to a contemporary novel, I aim to develop my own understanding and implementation of ecofeminist themes within my creative work ‘Above Ground’.
Embargoed until 17th February 2027
Keywords: 360201 Creative writing (incl. scriptwriting)